Clinical efficacy of non-pharmacological treatment of functional constipation: a systematic review and network meta-analysis - Shufa Tan; Chengtao Peng; Xin Lin; Chuanyue Peng; Yunyi Yang; Shuang Liu; Ling Huang; Yuhong Bian; Yuwei Li; Chen Xu (Frontiers in Cellular and Infection Microbiology)
IntroductionThe purpose of this study is to compare the relative effectiveness and safety of non-pharmacological interventions for the treatment of functional constipation (FC).MethodsWe searched Pubmed, Embase, Cochrane, and Web of Science databases for randomized controlled trials published from 2010 to November 2024. The quality of the included studies was evaluated using the Cochrane bias risk tool and Review Manager 5.4, and the evidence was graded using GRADEPro. A network meta-analysis (NMA) was conducted using R Studio, and the surface under the cumulative ranking curve (SUCRA) was used to rank the included drugs for each outcome measure to compare the clinical efficacy of different treatment methods for chronic functional constipation.ResultsA total of 29 RCT studies were included, with a total of 4389 patients with functional constipation who were randomly assigned to receive placebo or one of the nine different non-pharmacological treatment methods. The assessment of bias risk showed that the bias risk of most included studies was low. The results showed that the first-ranked treatment method for clinical efficacy was acupuncture; the first-ranked treatment method for changes in spontaneous bowel movement (SBM) and complete spontaneous bowel movement (CSBM) was fecal microbiota transplantation (FMT); the first-ranked treatment method for changes in the Bristol Stool Form Scale (BSFS) score was FMT; the first-ranked treatment method for changes in the Patient Assessment of Constipation Quality of Life (PAC-QOL) score after treatment was the Vibration capsule; the first-ranked treatment method for changes in the Patient Assessment of Constipation Symptoms (PAC-SYM) score after treatment was percutaneous electrical stimulation; and the treatment method with the lowest incidence of adverse reactions was probiotics.ConclusionBased on the SUCRA values and NMA results, we found that FMT showed better effects and higher safety on BSFS scores, SBM, and CSBM. In addition, acupuncture showed a good clinical efficacy. We hypothesize that the combination of FMT and acupuncture may be an effective and safe treatment option for functional constipation, but further high-quality clinical studies are needed to confirm this.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024625747.